El bien jurídico en el delito de colusión - Pariona Arana, Raúl (2022)
The determination of the legal interest in the crime of collusion is relevant for the legitimate application of criminal law. The validity of the principle of protection of legal assets is relevant in the field of crimes against the public administration, where simple administrative infractions are often sanctioned such as crimes. Therefore, in the case of the collusion, the punishment is based on reasons that go beyond the mere breach of duties or the presence of administrative irregularities. Legitimacy is based here on the harmfulness of the collusion act.